ANALYSIS OF SPEAKING ABILITIES OF EARLY CHILDREN 5-6 YEARS OLD USING HAND Puppet MEDIA AT ANATA SINGGANI POMBEWE KINDERGARTEN - Endera, Fatma Susianingsih; Yudana, I Wayan; Murniasih, Ni Putu (STAH Dharma Sentana Sulawesi Tengah, 2025)
Speaking ability is the process of communicating through the articulation of sounds to convey meaning so that the message can be understood by others. This study examines the use of hand puppet media in developing children's speaking abilities at TK Anata Singgani, as well as the challenges faced by teachers when using hand puppet media in the same institution. The theoretical foundation used in this research is motivation theory. The aim of this study is to understand how hand puppet media is used and what obstacles teachers encounter in enhancing children's speaking abilities at TK Anata Singgani. The findings of the study indicate that the use of hand puppet media contributes to the development of children's speaking skills at TK Anata Singgani. However, several challenges are faced by teachers when using this media, including: a lack of hand puppet resources, limited responses from students, insufficient storytelling skills among teachers, children’s lack of focus, and the fact that not all children are able to understand the stories or sentences conveyed through hand puppet media.